What Do Basic Education Teachers Participating in Creative Drama Instructor/Leadership Program Think About Creative Drama Method? - Esat Yildirim (Mimbar Sekolah Dasar, 2023)
The main purpose of this research is to reveal how basic education teachers who educate students who are the subjects of the educational system participating in the Private Creative Drama Instructor/Leadership program make sense of the creative drama method and their experiences with this process. Data were collected through interviews and participant diaries. The interviews were made face to face with the teachers in a private room and were recorded with a voice recorder. The collected data were analyzed by inductive content analysis. Participants emphasized the strengths of using creative drama as a method at the end of the course. As a result of the interview, teachers stated that drama education and applications contribute to skills such as language, decision-making and expression skills and have a positive effect on personal development. It can be said that the data obtained in the interview and the data obtained in the participant diaries are consistent and support each other. In addition, the harmony of the group and the members of the group getting to know each other is very important in drama practice, but it is recommended that teachers and researchers who will practice drama should make the place where the practice will be held convenient and appropriate.